Application-Based Crossword Puzzles: Players’ Perception and Vocabulary Retention - Dzulfikri Dzulfikri (Universitas Syiah Kuala, 2016)
This study investigates the perceptions of students towards Application-Based Crossword Puzzles and how playing this game can affect the development of vocabulary amongst students. Drawing on Vygostky’s Socio-Cultural Theory which states that the human mind is mediated by cultural artifacts, the nature of this game poses challenges and builds curiosity, allowing players to pay more attention to the words to fill in the boxes which subsequently enhances their retention of vocabulary. This game has very good potential to build positive perceptions and to develop cognition in the linguistic domain of players, i.e. the amount of their vocabulary. In this study, the researcher conducted interviews with eligible or selected student players to find out their perceptions toward this game and administered a vocabulary test to find out how this game had added to the retention in memory of new words acquired by the players from the game. The study findings showed that the participants perceive this game positively and it affects the players’ vocabulary retention positively as indicated by their test results. It is recommended that English teachers consider using Application-Based Crossword Puzzles to help students build their vocabularies especially as part of extracurricular activities.